Impact of High-K and Gate-to-Drain Spacing in InGaAs/InAs/InGaAs-based DG-MOS-HEMT for Low-leakage and High-frequency Applications. Issue 3 (3rd April 2023) - Baskaran, S.; Saravana Kumar, R.; Saminathan, V.; Poornachandran, R.; Mohan Kumar, N.; Janakiraman, V.
ABSTRACT: In this work, the impact of high-K and gate-to-drain spacing ( Lgd ) in InAs-based double-gate metal oxide semiconductor high-electron-mobility transistor (DG-MOS-HEMT) is analyzed for low-loss and high-frequency applications using 2D Sentaurus TCAD simulation. In this device, HfO2 is utilized as the dielectric material and that offers a reduced leakage current. The device with small gate-to-drain spacing ( Lgd ) gives an exquisite device operation in enhancement mode (E-mode) operation with a positive threshold voltage ( VT ) of 0.1223 V, the high drain current ( Ids, sat ) of 1.38 mA/µm, transconductance ( gm ) of 1.59 ms/µm, and sub-threshold slope ( SS ) of 75 mV/dec is achieved. These superior properties in this device show a high cut-off frequency ( fT ) of 547 GHz and the maximum oscillation frequency of ( fmax ) of 740 GHz. The numerical device simulation results show that DG-MOS-HEMT with HfO2 as dielectric offers a remarkable control of leakage current and makes it suitable for low-power, low-noise, and high-frequency applications.